Research on Causes and Countermeasures of Audit Failure – Taking Huishan Dairy as an Example - Jiao, Yue; Wang, Xiaoyi (Economics & Management Review, 2024)
In recent years, the academic field has been saturated with research on audit failures, but the understanding of audit failures of agricultural companies still needs to be deepened due to the difficulty of field investigation and the close relationship between biological assets and the natural environment. This paper chooses the agricultural company – Huishan Dairy as an entry point, through the way of a case study, analyzes the audit failure problems and reasons, puts forward the targeted improvement measures for the audit of agricultural companies to bring some inspiration, in order to solve the practical problems encountered in the audit work.